PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN ORGANIZATION CITIZENSHIP BEHAVIOR PADA DINAS PENDIDIKAN KEBUDAYAAN, PEMUDA DAN OLAHRAGA KABUPATEN BIMA - Rahmatia Rahmatia; I. N Nugraha; S Julaeha (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to determine the effect of work environment variables on performance with Organization Citizenship Behavior (OCB) as an intervening variable at the Department of Education, Culture, Youth and Sports, Bima Regency. The type of research is explanatory quantitative with primary data sources using data coloction methods namely census for sampling tecnique used saturated sampling is the entrire populations is a sample. the number of research samples as many as 66 employees of the State Civil Apparatus (ASN) Dikpora as respondents with data collection techniques using a Likert scale questionnaire and then analyzed with SPSS version 25. The hypothesis that the work environment has a significant effect on employee performance with Organization Citizenship Behavior (OCB) as the intervening variable was rejected. The results of analysis prove that the work enviroment has a greater direct influence on employee performance. This means that Organization Citizenship Behavior (OCB) is not an intervening variable between variable work environment has a significant effect on employee performance at the Departement of Education, Culture, Youth and Sports, Bima Regency.